Features of the aminomethylation of 7-hydroxy-4'-fluoroisoflavones with primary amines - Bondarenko, Svetlana; Frasinyuk, Mihaylo; Khilya, Volodimir (My University, 2010)
The behavior of 7-hydroxy-4'-fluoroisoflavones under the conditions of the Mannich reaction with primary amines was studied. New 9-alkyl-substituted 3-(4-fluorophenyl)-9,10-dihydro-4H,8H-chromeno-[8,7-e][1,3]oxazin-4-ones were synthesized. A method was developed for the synthesis of 8-amino- methyl derivatives of isoflavones.
Keywords: isoflavone; aminomethylation; electrophilic substitution; ізофлавон; електрофільне заміщення; амінометилювання; кафедра харчової хімії